2016
DOI: 10.1002/chir.22568
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Separations of Pyriproxyfen and its Six Chiral Metabolites by High‐Performance Liquid Chromatography

Abstract: Pyriproxyfen is a chiral insecticide, and over 10 metabolites have been identified in the environment. In this work the separations of the enantiomers of pyriproxyfen and its six chiral metabolites were studied by high-performance liquid chromatography (HPLC). Both normal phase and reverse phase were applied using the chiral columns Chiralpak IA, Chiralpak IB, Chiralpak IC, Chiralcel OD, Chiralcel OD-RH, Chiralpak AY-H, Chiralpak AD-H, Chiracel OJ-H, (R,R)-Whelk-O 1, and Lux Cellulose-3. The effects of the chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Many papers are aimed to the determination of herbicides [103,104,108,110], insecticides [48,100,97,107,105], fungicides [102,109,106,101,99] or antiviral drugs [98] from many different chemical families, including aryloxyphenoxy propionic acids, pyridines, oxadiazines, phenylpyrazoles, acylalanines, pyrethroids, triazoles, α-aminophosphonates, sulfoxides, etc. have been determinated in environmental or food samples (soil, natural waters, fruits, vegetables, etc.).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Many papers are aimed to the determination of herbicides [103,104,108,110], insecticides [48,100,97,107,105], fungicides [102,109,106,101,99] or antiviral drugs [98] from many different chemical families, including aryloxyphenoxy propionic acids, pyridines, oxadiazines, phenylpyrazoles, acylalanines, pyrethroids, triazoles, α-aminophosphonates, sulfoxides, etc. have been determinated in environmental or food samples (soil, natural waters, fruits, vegetables, etc.).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…have also been determined, especially in commercial products or biological samples (pharmaceutical formulations, human urine, human or animal blood, human plasma, animal serum, etc.). Another heterogeneous group of analytes, including connectors for building metal-organic frameworks [116,117,124], intermediates for the synthesis of pharmaceuticals [111], natural and synthetic compounds [39,113,121,120], biological compounds [82,112,58,71,78,86,[61][62][63]77,75], natural alkaloids [121], biomolecules [115,54], organometallic compounds [119] and chiral metabolites [103,108,100,97,102,59,63,52] has been enantioseparated with these immobilized polysaccharides CSPs (see Table 2-4). Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The annual production of PhOP in United Kingdom was reported to be about 30 tons in 2007 19 . Studies have shown that PhOP can be released as a monomer or metabolite from PhOP-containing products 20 – 22 . Masao et al (2005) investigated the metabolism of the insect growth regulator pyriproxyfen in tomatoes plants and found that PhOP was detectable in tomato fruit as a metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharide and brush-type CSPs are the two most widely used ones in many commercialized chiral columns. 10,11 Immobilized and coated polysaccharide CSPs have high enantiomeric selectivity and large load for many types of racemates. [12][13][14] Since the brush-type CSPs are formed by covalent bonding, the stability is excellent.…”
Section: Introductionmentioning
confidence: 99%